Near infrared (NIR) hyperspectral imaging for evaluation of whole maize kernels: chemometrics for exploration and classification - Williams, Paul James (Stellenbosch : University of Stellenbosch, 2009)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2009.